2011
DOI: 10.1007/s00216-011-5598-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a dispersive liquid–liquid microextraction method for the analysis of benzotriazoles and benzothiazoles in water samples

Abstract: A simple and rapid dispersive liquid-liquid microextraction method has been developed for the determination of 11 benzotriazoles and benzothiazoles in water samples. Tri-n-butylphosphate (TBP) was used as extractant, thus avoiding the use of toxic water-immiscible chlorinated solvents. The influence of several variables (e.g., type and volume of dispersant and extraction solvents, sample pH, ionic strength, etc.) on the performance of the sample preparation step was systematically evaluated. Analytical determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 42 publications
3
32
1
Order By: Relevance
“…The results revealed that extraction efficiencies of these solvents were comparable and higher than using the chlorinated solvents. Good sensitivity with relatively lower limit of detection was also obtained [22][23][24][25][26]. Compared to chlorinated solvents, some of the brominated and iodinated solvents have lower toxicity [22,26,27].…”
Section: Introductionmentioning
confidence: 77%
“…The results revealed that extraction efficiencies of these solvents were comparable and higher than using the chlorinated solvents. Good sensitivity with relatively lower limit of detection was also obtained [22][23][24][25][26]. Compared to chlorinated solvents, some of the brominated and iodinated solvents have lower toxicity [22,26,27].…”
Section: Introductionmentioning
confidence: 77%
“…Water was initially selected in view of the high polarity and water solubility of these compounds, and considering their relatively low K ow [1,8].…”
Section: Resultsmentioning
confidence: 99%
“…Differently from other micropollutants such as sulfa drugs [2], herbicides [3] and fluoroquinolone antibiotics [4,5], also photochemistry under natural conditions as abiotic transformation path is scarcely efficient in their removal from contaminated ecosystems, as reported for BTRs [6], unless working under hard irradiation conditions or advanced oxidation processes [7]. Moreover, the relatively low octanol-water partition coefficients (K ow ) strongly favour the mobility in water phase [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, an environment at pH 2-3 favors the extracting of Co, Ni, Cu, Nb, Mo, Cd, Sn, In, Te, Pb, and Bi, whereas pH 3-4 is particularly effective at isolating Be, Sc, Ti, Cr, V, Co, Ni, Cu, Zn, Ga, Ge, As, Zr, Nb, Sn, In, Te, REE (rare earth elements), Hf, Ta, W, Tl, Pb, Bi, Th, and U from a matrix solution. 17 The selectivity of extraction can further improved by replacing APDC with some other specific extractant, for example, tri-n-butylphosphate for aromatic compo-nents, 16,18 diethyldithiocarbamate for Cr, 6 and crown ethers for elements in groups IA and IIA. 19,20 On the other hand, minimizing the spreading of the droplet will require to the selection of an appropriate substrate.…”
Section: Factors That Might Further Improve the Overall Enhancementmentioning
confidence: 99%